Trainee Work System Design In The Hot Kitchen Section Of Novotel Hotel Tangerang - Nabila Rizqy Fahira; Ersy Ervina; Umi Sumarsih (Publikasi Indonesia, 2023)
Work System Design is a work system design made by the company based on company factors and goals, which will later be used as an essential reference regarding task descriptions for each employee. Task descriptions help define each job from the department so that the work undertaken is systematic to achieve the company's goals. Seeing the importance of this, the author researched the work system design at Novotel Tangerang Hotel, especially in the Food and Beverage Product Department for trainees in the Hot Kitchen. The background of this problem is that the work done by trainees in the hot kitchen is still not well structured. The problem is that the company has no written trainee work system design. This research uses qualitative methods with data collection techniques in the form of observation, interviews, and literature studies with the help of voice recording devices and cameras to answer problem formulations. The result obtained is that the work system design for trainees is formed based on organisational culture or in the sense that there is no work system design for trainees in writing by the company because work for trainees can change over time